Inflammation in schizophrenia: A question of balance. (August 2015) - Leza, Juan C.; García-Bueno, Borja; Bioque, Miquel; Arango, Celso; Parellada, Mara; Do, Kim; O'Donnell, Patricio; Bernardo, Miguel
Highlights: Inflammation and oxido/nitrosative stress appear in blood and brain in patients with schizophrenia. A disbalance in pro/anti-inflammatory mechanisms occurs in peripheral blood cells in schizophrenia. New pharmacological strategies add on antipsychotics might prevent inflammatory consequences in schizophrenia. Abstract: In the past decade, there has been renewed interest in immune/inflammatory changes and their associated oxidative/nitrosative consequences as key pathophysiological mechanisms in schizophrenia and related disorders. Both brain cell components (microglia, astrocytes, and neurons) and peripheral immune cells have been implicated in inflammation and the resulting oxidative/nitrosative stress (O&NS) in schizophrenia. Furthermore, down-regulation of endogenous antioxidant and anti-inflammatory mechanisms has been identified in biological samples from patients, although the degree and progression of the inflammatory process and the nature of its self-regulatory mechanisms vary from early onset to full-blown disease. This review focuses on the interactions between inflammation and O&NS, their damaging consequences for brain cells in schizophrenia, the possible origins of inflammation and increased O&NS in the disorder, and current pharmacological strategies to deal with these processes (mainly treatments with anti-inflammatory or antioxidant drugs as add-ons to antipsychotics).